Multi-Objective Optimization of a Rectangular Structured Linear, Actuator Based on Taguchi Method - Jawad, Muhammad; Yu, Haitao; Farrokh, Fariba; Ahmad, Zahoor (Applied Computational Electromagnetics Society Journal (ACES), 2026)
This paper introduces an innovative rectangular structured Linear Oscillating Machine (LOM) featuring an innovative arrangement of permanent magnets (PMs) which are positioned on the mover. A sinusoidal magnet arrangement (SMA) is chosen to minimize PM materials while ensuring the performance parameter, in terms of electromagnetic force, remains unaffected. The focus of the design is to reduce the cogging force and enhance the electromagnetic force to the PM mass ratio. The optimization is accomplished by utilizing design-of-experiment (DOE) Taguchi method optimization for a linear actuator, along with the finite element method (FEM). A multi-objective optimization approach is employed to refine the parameters of the linear actuator, focusing on the maximum force, the force-to-PM-weight ratio, and minimizing cogging force. By identifying the most effective parameters, an appropriate case with high sensitivity and accuracy is selected. The output parameters, like electromagnetic force and stroke of the proposed optimization approach, score very well, while the design is simply structured due to the utilization of a rectangular structured core part. The proposed design significantly reduces the cogging force to an exceptionally low level, enhancing performance and reliability.